Fracture load of complete-arch implant-supported prostheses reinforced with nylon-silica mesh: An in vitro study - Gonçalves, Fernanda de Cássia Papaiz; Amaral, Marina; Borges, Alexandre Luiz Souto [UNESP]; Gonçalves, Luiz Fernando Martins; Paes-Junior, Tarcisio José de Arruda [UNESP] (Elsevier, 2018)
Statement of problem: Complete-arch implant-supported prostheses without a framework have a high risk of failure: a straightforward and inexpensive reinforcement material, such as nylon mesh, could improve their longevity. Purpose: The purpose of this in vitro study was to evaluate a nylon-silica mesh compound on the fracture strength of acrylic resin and the fracture load of complete-arch implant-supported prostheses. Material and methods: Twenty-four complete mandibular arch implant-supported prostheses were divided into 2 groups according to cantilever length (molar and premolar) and subdivided into another 2 subgroups according to the presence or absence of reinforcing mesh. The specimens were submitted to a maximum load-to-fracture test in a universal testing machine, with a 100-N load cell, a 2 mm/min crosshead speed, and a spherical metal tip diameter of 4 mm at different points (molar and premolar). These were submitted to 1-way analysis of variance for repeated measurement and the post hoc Tukey multiple comparison test (α=.05). Results: The mean maximum load ±standard deviation for the molar group was 393.4 ±95.0 N with reinforcement and 305.4 ±76.3 N without reinforcement (P=.02); and for the premolar group was 1083.3 ±283.7 N with reinforcement and 605.3 ±90.5 N without reinforcement (P=.001). Conclusions: Reinforcement with nylon mesh increased the mean maximum load of implant-supported complete-arch prostheses at both cantilever lengths. The cantilever to the premolar (5 mm) presented the highest maximum load values to fracture.